Novel Pseudomonas aeruginosa Quorum-Sensing Inhibitors Identified in an Ultra-High-Throughput Screen - Ute Müh; Martín Schuster; Roger Heim; Ashvani K. Singh; Eric R. Olson; E. Peter Greenberg (2006)
The opportunistic pathogen Pseudomonas aeruginosa has two complete acyl-homoserine lactone (acyl-HSL) signaling systems, LasR-LasI and RhlR-RhlI. LasI catalyzes the synthesis of N-3-oxododecanoyl homoserine lactone (3OC12-HSL), and LasR is a transcription factor that requires 3OC12-HSL as a ligand. RhlI catalyzes the synthesis of N-butanoyl homoserine lactone (C4), and RhlR is a transcription factor that responds to C4. LasR and RhlR control the transcription of hundreds of P. aeruginosa genes, many of which are critical virulence determinants, and LasR is required for RhlR function. We developed an ultra-high-throughput cell-based assay to screen a library of approximately 200,000 compounds for inhibitors of LasR-dependent gene expression. Although the library contained a large variety of chemical structures, the two best inhibitors resembled the acyl-homoserine lactone molecule that normally binds to LasR. One compound, a tetrazole with a 12-carbon alkyl tail designated PD12, had a 50% inhibitory concentration (IC50) of 30 nM. The second compound, V-06-018, had an IC50 of 10 microM and is a phenyl ring with a 12-carbon alkyl tail. A microarray analysis showed that both compounds were general inhibitors of quorum sensing, i.e., the expression levels of most LasR-dependent genes were affected. Both compounds also inhibited the production of two quorum-sensing-dependent virulence factors, elastase and pyocyanin. These compounds should be useful for studies of LasR-dependent gene regulation and might serve as scaffolds for the identification of new quorum-sensing modulators.